Visual Narrative as Strategy of Traditional Texts: A Study on Serat Menak - Lutfi, Mochtar; Satya Dewi, Trisna Kumala; Nugraha Putra, Gesang Manggala (Opción, 2019)
The study aims to investigate visual narrative as a strategy of traditional texts on Serat Menak via descriptive qualitative research methods. As a result, illumination and illustration images in the Serat Menak script show copyist creativity, mastery of color composition, and knowledge of puppet images. In conclusion, the illustrations in the Serat Menak script have a close relationship with the contents of the story.